"I Need More than Emotional Support!": An Exploration of Social Support for Domestic Violence - Abdullah, Fatimah; Nurani, Gita Aulia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Domestic violence (domestic violence) is a treatment that causes physical, mental and sexual injuries that occur in married women. This research was conducted to determine the form of social support provided in the surrounding environment. The method used in this study is qualitative phenomenology. In addition, the data collection methods and tools used in this study used semi-structured techniques and used problem mining (probing), namely by interviews. The subjects in this study were 6 female victims of domestic violence. The subject criteria are women who are married and have experienced domestic violence during their marriage. The results obtained from the interview results of the six subjects received 5 forms of social support, the first was emotional support in the form of physical presence, existence, sense of security, empathy, strengthening words and giving advice. The second is instrumental support in the form of materials and business capital. Forms of social support. Implication or recommendation?